Financial Incapacity of Patients with Mild Alzheimer’s Disease: What Neurologists Need to Know about Where the Impairment Lies - Vaitsa Giannouli; Magda Tsolaki (Neurology International, 2022)
Research in the last decade has focused on assessing financial capacity and incapacity mainly in old age, but new research has turned to address the question of how financial incapacity can be predicted by cognitive factors. The aim of this study was to identify which cognitive domains predict financial capacity and the relevant cognitive skills of patients with mild Alzheimer’s disease (AD) in order to assist neurologists in functional assessment and further patient referral. In this study, 109 patients diagnosed with mild AD were examined with a number of neuropsychological tests: Mini-Mental State Examination (MMSE), Functional Rating Scale for Symptoms of Dementia (FRSSD), Functional Cognitive Assessment Scale (FUCAS), Trail Making Test (TMT)-Part B, Rey-Osterrieth Complex Figure Test (ROCFT)-copy condition and delayed recall condition, Rey Auditory Verbal Learning Test (RAVLT), Boston Naming Test, Rivermead Behavioural Memory Test (RBMT), digit span forward and backward, WAIS-R digit symbol substitution test, Neuropsychiatric Inventory (NPI), Geriatric Depression Scale (GDS-15), and the Legal Capacity for Property Law Transactions Assessment Scale (LCPLTAS). LCPLTAS total score and relevant subdomains were best predicted only by the score of one item coming from MMSE: subtraction of serial sevens. This is the only measure of arithmetic testing in use for the Greek geriatric population. Financial capacity is severely impaired in the group of mild AD patients. In order to prevent financial exploitation cases, neurologists, neuropsychologists, psychiatrists, and geriatrists should pay close attention to the information from the relevant arithmetic question of MMSE, as it is one of the most widely administered screening tests in clinical settings.